Changes in soil organic carbon fractions after afforestation with xerophytic shrubs in the Tengger Desert, northern China. (8th January 2016) - Li, X. J.; Li, X. R.; Wang, X. P.; Yang, H. T.
Summary: Afforestation is an important means of controlling desertification and of restoring vegetation on land that has become desert. The procedure leads to changes in the dynamics of organic carbon (C) in the soil as xerophytic shrubs are established, but the dynamics are still poorly understood, partly because of the lack of long‐term observations. Progressive measures to bind sand dunes along the route of the Baotou–Lanzhou railway on the south eastern edge of the Tengger Desert in China, which were begun in 1956, provide the opportunity to study such changes. We sampled the topsoil (0–10 cm) from 10 sites that represent a chronosequence and vary in age from 1 to 57 years since sand‐binding measures and afforestation were begun. These measures evidently trapped increasing amounts of clay and silt, and with them increased the concentrations of both available phosphorus (P) and available potassium (K). By analysing the organic C in the samples we have been able to describe quantitatively the changes in several C fractions over time. We found that total C, its light and heavy fractions, dissolved C and microbial C all increase slowly at first after afforestation, then more rapidly, and then at a decreasing rate. They seem to be examples of logistic growth and could be described by logistic equations. The light fraction increased faster than the total C, as did the microbial C during the first 19 years. The light C fraction was the most sensitive for identifying changes in soil C after afforestation. Over the full 57 years, the contributions of the light and microbial fractions to total C increased, while those of the heavy fraction and dissolved C decreased. Our results suggest that the proportion of C in labile pools increased, but the proportion in stable pools decreased, which would increase the risk of substantial losses of C caused by potential global warming and human‐induced disturbances.